Pengaruh Foreign Direct Investment (FDI) Dan Ekspor Terhadap Pertumbuhan Ekonomi Di Indonesia Tahun 1990-2021 - Anggrya, Yenni; Destiani, Egi; Moniyana, Resha (Convergence: The Journal of Economic Development, 2023)
the purpose of this research is to see whether there is influence from Foreign Direct Investment (FDI) and Exports on Economic Growth in Indonesia. This study used a quantitative approach. The data used is secondary data sourced from the World Bank in the form of time series data from 1990-2021. The data is analyzed using the ECM (Error Correction Model) method to see the long-term and short-term effects of FDI and exports on economic growth. The results of this study indicate that the FDI variable has a positive but not significant effect on economic growth in the long and short term. The export variable has a negative and significant impact on economic growth both in the long term and in the short term. FDI and export variables simultaneously have a significant influence on economic growth in Indonesia.